2010
DOI: 10.1590/s0101-31222010000200001
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho fisiológico de sementes de soja de cultivares convencional e transgênica submetidas ao glifosato

Abstract: O objetivo do trabalho foi avaliar a qualidade fisiológica de sementes de soja convencional e transgênica, das cultivares CD 216 e CD 212RR, submetidas ao glifosato. As sementes foram embebidas nas doses de zero; 1,8; 3,6; 5,4 e 7,2 g.L-1 de equivalente ácido de glifosato durante meia hora. Foram realizados os testes de primeira contagem da germinação, germinação, condutividade elétrica, índice de velocidade de emergência, emergência de plântula, comprimento de raízes e parte aérea, massa de matéria seca total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
4
19
0
5
Order By: Relevance
“…Detection of these plants by the use of glyphosate is more difficult in the field or in the greenhouse. Some authors report problems of phytotoxicity, reduction in productivity and the presence of herbicide residue in plants and seeds, often causing losses in the commercial value and quality of the product (BERVALD et al, 2010;REIS et al, 2010). The selection of individual transgenic plants therefore requires methodologies that are easy, of low cost and not aggressive to nearby plants.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of these plants by the use of glyphosate is more difficult in the field or in the greenhouse. Some authors report problems of phytotoxicity, reduction in productivity and the presence of herbicide residue in plants and seeds, often causing losses in the commercial value and quality of the product (BERVALD et al, 2010;REIS et al, 2010). The selection of individual transgenic plants therefore requires methodologies that are easy, of low cost and not aggressive to nearby plants.…”
Section: Introductionmentioning
confidence: 99%
“…Comprimento de raízes e parte aérea das plân-tulas: no final do teste de emergência em areia, foi efetuada a medida das partes das plântulas emergidas (parte aérea e raiz), de dez plântulas normais, com auxílio de régua graduada, e os resultados foram expressos em milímetros (Vanzolini e Carvalho, 2002;Bervald et al, 2010).…”
Section: íNdice De Velocidade De Emergência (Ive)unclassified
“…Este é um herbicida sistêmico de ação total, não-seletivo, pós-emergente, amplamente utilizado na agricultura (Bervald et al, 2010). Na produção de soja convencional, em média, são necessárias duas ou três aplicações de defensivos em mistura, aumentando, consequentemente, o custo de mão-de-obra e matéria prima durante o processo produtivo.…”
Section: Introductionunclassified
“…Results corroborated by Marcandalli, Lazarini and Malaspina (2011) revealed that reduced seedling length resulted from hypocotyl and, especially, primary root shortening (0.880*** and 0.990***, respectively), according to Person's correlation test. According to Bervald et al (2010), photosynthesis does not occur in early stages of seedling development due to an early stage in formation of photosynthetic apparatus. That way, seedlings do not form amino acids that are essential in the synthesis of proteins and secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%